Microdermabrasion with controlled pressure for sensitive and thin skin: quantitative assessment of tissue safety and restoration of barrier function - Zhenzherukha, Oksana (Global Prosperity, 2025)
Abstract. The study is devoted to the assessment of tissue safety and the features of restoration of skin barrier properties after controlled microdermabrasion of patients with thin and sensitive skin. First of all, the aim of the article is to show the possibility of using such a procedure for the specified category of patients, as well as to reveal the specifics of using different approaches to its implementation. During the scientific search, general scientific methods of cognition were used: analysis and synthesis, induction, systematization and generalization. The results of the study demonstrate that the effect of controlled microdermabrasion on sensitive skin is carried out in stages. First, controlled microtrauma is induced. Then transient reactions are observed, which manifest themselves in the form of increased microrelief and erythema. The final stage is the restoration of surface structures, which is accompanied by an improvement in aesthetic characteristics. At the initial stage of recovery, a short-term increase in transepidermal water loss and erythema index is recorded, which is a manifestation of the physiological inflammatory response. After 48–72 hours, the indicators return to the baseline level or acquire positive dynamics. It was established that hydration stabilization and reduction of relief heterogeneity occur already on the third day after the session. The work also emphasizes the importance of individual selection of procedure parameters: abrasion force, vacuum pressure level and number of passes. This approach minimizes the risk of excessive inflammatory reaction. A conclusion is made on the feasibility of using personalized post-procedure protocols. In the first 72 hours, it is recommended to avoid potential irritants (the sun in particular) and ensure active hydration. The practical significance of the work lies in the formation of algorithms for the safe use of microdermabrasion for patients with increased skin sensitivity. This allows to reduce risks and improve therapeutic results.